PEMBELAJARAN MENULIS TEKS EKSPOSISI DENGAN MENGGUNAKAN MODEL THINK TALK WRITE (TTW) - Sri Rahayu Indra Yanti Putri; Anisa Maulana Ulpa; Mekar Ismayani (IKIP Siliwangi, 2019)
This research is motivated by the fact that the difficulties faced by students in producing when expressing ideas and ideas in determining the language elements of the exposition text. more students do not understand the exposition text than students who already understand how to write exposition text, so researchers offer a learning model Think talk write as a solution to overcome this problem. Using the model, students can learn in a structured and not boring way, because this model is structured, students will be able to capture and absorb learning well. This study was conducted to find out 1) whether the think talk writes model can foster the skill of writing exposition text 2) whether there are differences before or after using the think talk write model. The aim of the researcher for this writing skill is to make learning in the classroom effective. Therefore, researchers used the think talk write (TTW) model as a solution to these problems. This study uses the One-Group Pretest-Posttest Design method, the data obtained from the results of the pretest and posttest. The average results of the pretest students get 68 and the average posttest results obtained are 78. Based on the results of the analysis seen differences before and after treatment. In other words, the model (TTW) is effectively used in learning exposition text writing.